Roles of MicroRNA-21 in Skin Wound Healing: A Comprehensive Review - Xie, Jie; Wu, Weizhou; Zheng, Liying; Lin, Xuesong; Tai, Yuncheng; Wang, Yajie; Wang, Le (Frontiers in Pharmacology, 2022)
MicroRNA-21 (miR-21), one of the early mammalian miRNAs identified, has been detected to be upregulated in multiple biological processes. Increasing evidence has demonstrated the potential values of miR-21 in cutaneous damage and skin wound healing, but lack of a review article to summarize the current evidence on this issue. Based on this review, relevant studies demonstrated that miR-21 played an essential role in wound healing by constituting a complex network with its targeted genes (i.e., PTEN, RECK. SPRY1/2, NF-κB, and TIMP3) and the cascaded signaling pathways (i.e., MAPK/ERK, PI3K/Akt, Wnt/β-catenin/MMP-7, and TGF-β/Smad7-Smad2/3 signalings). The treatment effectiveness developed by miR-21 might be associated with the promotion of the fibroblast differentiation, the improvement of angiogenesis, enhancement of the collagen synthesis, and the re-epithelialization of the wound. Currently, miRNA nanocarrier systems have been developed, supporting the feasibility clinical feasibility of such miR-21-based therapy. After further investigations, miR-21 may serve as a potential therapeutic target for wound healing.